Scenario of Plant Breeding in Nepal and Its Application in Rice - Bigyan K. C.; Rishav Pandit; Bishnu Prasad Kandel; Kanchan Kumar K. C.; Arpana K. C.; Mukti Ram Poudel (International Journal of Agronomy)
Rice, the number one staple food crop of Nepal, contributes nearly 20% to the agricultural gross domestic product, almost 7% to gross domestic product, and supplies with 40% of the food calorie consumption of Nepalese people. Despite of increasing production, the national demand of rice cannot be fulfilled, and billions of rupees are spent yearly for importing rice from India. This article reviews history, recent scenario, prospects, and importance of rice breeding research in Nepal for self-sufficiency. Though plant breeding inception point in Nepal was 1951, the systematic research in rice was started from 1972 after the establishment of the National Rice Research Program. Introduction and evaluation of high yielding exotic germplasm of rice was the initial rice breeding activities. After analysing several foreign materials, CH-45 variety of rice was first recommended in 1959. Nepal Agriculture Research Council (NARC), the leading organisation for rice varietal improvement to date, has been doing rice research activities such as germplasm conservation, exchange, varietal development, verification of technologies, and knowledge updates in collaboration with various organizations. International Rice Research Institute (IRRI), since 1966, has been playing an important role in Nepal’s rice research. Major plant breeding achievements are introduction of exotic materials and their evaluation, local landraces identification, collection and analysis, crossing of local landraces with exotic genetic materials, heterosis breeding, tissue culture technology, genetic marker technology, and National Genebank. RAPD and SSR, DNA-based markers, are mostly used for diversity appraisal and selecting desirable genotypes. Integration of advanced tools such as genetic engineering, bioinformatics, protoplast fusion, and SNP markers could not be still applied in rice research and development. Hence, emphasis should be given to improve the capacity and abilities of the rice scientists and should release more short duration, drought, and submergence-tolerant rice varieties by optimum utilisation of local landraces combining modern and conventional breeding.